Maximum Power Point Tracking to Increase the Power Production and Treatment Efficiency of a Continuously Operated Flat‐Plate Microbial Fuel Cell. Issue 11 (4th August 2016) - Song, Young Eun; Boghani, Hitesh C.; Kim, Hong Suck; Kim, Byung Goon; Lee, Taeho; Jeon, Byong‐Hun; Premier, Giuliano C.; Kim, Jung Rae
Abstract: A logic‐based maximum power point tracking (MPPT) and LabVIEW interface for digitally controlled variable resistive load were developed and applied to a continuously operating flat‐plate microbial fuel cell (FPM). The interaction between the designed MPPT algorithm and electrochemically active microbial performance on the electrode was demonstrated to track the maximal performance of FPM system. MPPT could dynamically derive the optimal performance from varied operating conditions of FPMs such as organic concentration, flow rate, and sampling interval, and produce a maximum power density of 88.0 W m −3 . The results provide essential information to build an automatic control strategy to achieve the maximum performance from field scale microbial fuel cells for applications to sustainable bioenergy recovery from various biomass feedstocks. Abstract : Maximum power point tracking for MFCs : Microbial fuel cells (MFCs) can generate electricity from various organic materials and wastewaters by using a dynamic exoelectrogenic biocatalyst. A logic‐based algorithm to achieve maximum power point tracking (MPPT) for MFC interfaced to a digitally actuated variable resistive load is developed. The effects of operational parameters such as organic loading rate (OLR), hydraulic retention time (HRT), and sampling interval (SI) are examined.